2022
DOI: 10.3389/fspor.2022.814975
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Muscle Deoxygenation in Aerobically Fit Subjects During Exhaustive Exercise Is Associated With the ACE Insertion Allele

Abstract: IntroductionThe insertion/deletion (I/D) polymorphism in the gene for the major regulator of vascular tone, angiotensin-converting enzyme-insertion/deletion (ACE-I/D) affects muscle capillarization and mitochondrial biogenesis with endurance training. We tested whether changes of leg muscle oxygen saturation (SmO2) during exhaustive exercise and recovery would depend on the aerobic fitness status and the ACE I/D polymorphism.MethodsIn total, 34 healthy subjects (age: 31.8 ± 10.2 years, 17 male, 17 female) perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The implicated molecular processes possibly involve altered intracellular angiotensin and insulin signaling, which may lower glucose uptake and expression of glucose metabolism associated gene alike reported for the pharmacological inhibition of ACE ( Henriksen and Jacob 2003 ; Mathes et al, 2015 ). Intriguingly, variability in anatomical and functional aspects of aerobic glucose and lipid metabolism in contracting knee extensor muscle is associated with the ACE-I/D genotype in interaction with the aerobic fitness state ( Vaughan et al, 2013 ; Valdivieso et al, 2017 ; Gasser et al, 2022 ). For instance, higher increments in blood glucose concentration, respiration exchange ratio and glycogen depletion have been reported for ACE-DD genotypes during exhaustive one-legged exercise of healthy individuals, when conversely a higher degree of muscle deoxygenation and higher volume densities of mitochondria and intra-myocellular lipids are detected in aerobically fit ACE I-allele carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The implicated molecular processes possibly involve altered intracellular angiotensin and insulin signaling, which may lower glucose uptake and expression of glucose metabolism associated gene alike reported for the pharmacological inhibition of ACE ( Henriksen and Jacob 2003 ; Mathes et al, 2015 ). Intriguingly, variability in anatomical and functional aspects of aerobic glucose and lipid metabolism in contracting knee extensor muscle is associated with the ACE-I/D genotype in interaction with the aerobic fitness state ( Vaughan et al, 2013 ; Valdivieso et al, 2017 ; Gasser et al, 2022 ). For instance, higher increments in blood glucose concentration, respiration exchange ratio and glycogen depletion have been reported for ACE-DD genotypes during exhaustive one-legged exercise of healthy individuals, when conversely a higher degree of muscle deoxygenation and higher volume densities of mitochondria and intra-myocellular lipids are detected in aerobically fit ACE I-allele carriers.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly interesting as eccentric contractions can enhance the oxygen deficit of recruited leg muscles and since the volume content of mitochondria is known to deteriorate after endurance-type training under eccentric load [ 40 , 41 , 42 ]. The underlying mechanism is not fully elucidated but may involve a reduced haemoglobin content due to the underperfusion of muscle that is strained with intense eccentric contraction, and this may lead to possible mechanical damage that necessitates an adaptive cycle to repair and re-establish damaged cell structures, including mitochondria [ 40 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Abraham et al 13 observed a significantly higher baseline VO 2peak in 57 patients with congestive stable heart failure having the I/I genotype compared to carriers of the D allele, and the ACE I allele has been extensively linked to enhanced endurance performance in healthy individuals 8 , 14 . To date, the underlying physiological mechanisms remain largely unresolved, but accumulating evidence suggests that the potential association between the ACE genotype and performance-related phenotypes is related to ACE genotype-dependent modulations of muscular efficiency 15 20 , plausibly through ACE activity-dependent regulation of local nitric oxide bioavailability, which has been demonstrated to influence mitochondrial respiration and, consequently, metabolic efficiency 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%